Deporting the Pardoned - Cade, Jason A. (2012)
Federal immigration laws make noncitizens deportable on the basis of state criminal convictions. Historically, Congress implemented this scheme in ways that respected the states’ sovereignty over their criminal laws. As more recent federal laws have been interpreted, however, a state’s decision to pardon, expunge, or otherwise set-aside a conviction under state law will often have no effect on the federal government’s determination to use that conviction as a basis for deportation. While scholars have shown significant interest in state and local laws regulating immigrants, few have considered the federalism implications of federal rules that ignore a state’s authority to determine the continuing validity of its own convictions. This Article contends that limitations on the preclusive effect of pardons, expungements, appeals, and similar post-conviction processes undermine sovereign interests in maintaining the integrity of the criminal justice system, calibrating justice, fostering rehabilitation, and deciding where to allocate resources. In light of the interests at stake, Congress should be required to clearly express its intent to override pardons and related state post-conviction procedures. A federalism-based clear statement rule for statutory provisions that restrict generally applicable criminal processes would not constrain Congress’s power to set immigration policy, because Congress remains free to make its intent clear in the statute. But the rule would ensure that Congress, rather than an administrative agency, has made the deliberative choice to upset the usual constitutional balance of federal and state power